Data analysis model for solar energy system design in different climatic regions - Balo, Figen; Sua, Lutfu S. (Springer International Publishing, 2020)
The traditional energy source-related problems bring out the sustainable energy sources’ utilization. Limited amount of resources as well as ecological issues play a significant role in the choice of sustainable energy sources. Yet nowadays, rather than ecological requirements, renewable energy use has become increasingly significant on account of these strategies utilized by advanced nations to supply their power needs. Consequently, over the past two decades, all the countries have been aiming to raise the sustainable power’s share among other power generation methodologies to attain power independence. In this chapter, sun’s power potential is investigated in a comprehensive assessment for two main provinces with the largest energy consumption in Turkey. The analysis is performed to plan a photovoltaic (PV) system for maximal performance under climate circumstances in the country. Different panels are analyzed to obtain the ones that are more effective than the others under the conditions in which the system is established. This chapter’s purpose is to generate a mathematical model of a PV system design under a set of circumstances and find the most efficient and appropriate panel choice under the environmental circumstances to obtain conclusions closer to PV system’s actual ecologic circumstances. © Springer Nature Switzerland AG 2020.
Keywords: Data analysis; Panel efficiency; Photovoltaic systems; Renewable energy; Solar energy; Sustainability